2013
DOI: 10.1080/14616688.2012.675515
|View full text |Cite
|
Sign up to set email alerts
|

The Civil Rights Movement and the Future of the National Park System in a Racially Diverse America

Abstract: The U.S. National Park System contains places of world-renowned beauty and tremendous historical significance that represent some of the central values and experiences in American culture, democracy, and freedom for everyone, for all time. However, the vast majority of visitors to these parks are white, which has increasingly been seen as a problem as it suggests a lack of full participation by all members of society. While there are several perspectives on low minority visitation, it is possible that park pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…They carefully planned their trips to avoid such locations, traveled with large groups, used established accommodations, and visited places where family or friends live. These travel patterns echo the findings from existing studies (Floyd 1999;Mandala Research 2011;Philipp 1994;Taylor, Grandjean, and Gramann 2011;Weber and Sultana 2013;Williams and Chacko 2008). Thus, this study revealed African Americans' distinctive travel patterns serve as specific defensive strategies for coping with longstanding racial oppression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They carefully planned their trips to avoid such locations, traveled with large groups, used established accommodations, and visited places where family or friends live. These travel patterns echo the findings from existing studies (Floyd 1999;Mandala Research 2011;Philipp 1994;Taylor, Grandjean, and Gramann 2011;Weber and Sultana 2013;Williams and Chacko 2008). Thus, this study revealed African Americans' distinctive travel patterns serve as specific defensive strategies for coping with longstanding racial oppression.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have documented that compared to white Americans, African Americans tend to travel shorter distances with a group of people, avoid unplanned stops, eat at well-known restaurant chains, and visit destinations specific to African American heritage (Mandala Research 2011; Philipp 1994; Williams and Chacko 2008). Moreover, African Americans have the lowest rate of national park visitation, and they are usually the most underrepresented racial group in America’s great outdoors (Floyd 1999; Taylor, Grandjean, and Gramann 2011; Weber and Sultana 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The main constraints cited for not having visited a national forest primarily aligned with those most often cited for not visiting the forest more often (e.g., lack of time [13], money, distance [6], or transportation [13]). The exceptions to the set of constraints for lack of lifetime visitation include a lack of interest, cited as the second-highest constraint, and lack of information.…”
Section: Discussionmentioning
confidence: 93%
“…Research focused on equitable recreation participation in European countries is less abundant [2,3]. The U.S.-based research has consistently indicated that members of racial and ethnic minorities are not proportionally represented from proximate geographic areas among the visitors to federally managed natural resource areas, including national parks and national forests [4][5][6]. Although efforts in natural resource recreation management agencies have focused on increasing representation of ethnic and racial minorities to address concerns over equity, much remains to be done [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Those who visit the parks, however, increasingly do not reflect America's diverse cultural composition. In particular, visitors represent a less racially/ethnically diverse microcosm (i.e., mainly non-Hispanic White) than the American public (Taylor, Grandjean, & Anatchkova, 2011a;Weber & Sultana, 2013a). Replicating recreation trends reported for decades (Chavez, 2000;Gómez & Malega, 2007;Manning, 2011;Solop, Hagen, & Ostergren, 2003), recent studies in the national parks (Stodolska, Shinew, Floyd, & Walker, 2014;Taylor, Grandjean, & Gramann, 2011b) have found disparate visitation rates between non-Hispanic Whites and other groups.…”
mentioning
confidence: 99%